Clinical Presentation and Long‐Term Survival Outcomes of Patients With Monoclonal Gammopathy of Renal Significance (MGRS): A Multicenter Retrospective Study - K. Mancuso; R. Mina; S. Rocchi; E. Antonioli; M. T. Petrucci; F. Fazio; A. Gozzetti; M. Salvini; C. S. Cartia; G. Bertuglia; F. Patriarca; A. B. Dalla Palma; et al. (Cancer Medicine)
ABSTRACT Introduction MGRS are new rare clinical entities, whose recognition and optimal management is evolving. Methods To implement real‐life data, we retrospectively analysed a multicentre cohort of 60 patients with renal biopsy‐proven MGRS receiving mainly novel treatments (between 2006 and 2021) in eight Italian centres. Based on renal biopsy, patients were divided into two subgroups: AL amyloidosis (70%, n = 42) and other‐MGRS (30%, n = 18). Results Baseline characteristics follow typical manifestations of MGRS disorders in terms of small clonal burden, laboratory and clinical features. More patients with AL amyloidosis had monotypic lambda light‐chain disease, estimated glomerular filtration rate (eGFR) ≥ 60 mL/min and nephrotic proteinuria than other‐MGRS group. The most widely used drug was bortezomib, and about one‐third of patients underwent ASCT. Overall response rate was 86% with no differences in the two subgroups. However, high‐quality hematologic responses ≥very good partial response (VGPR) were greater in AL amyloidosis than in other‐MGRS group (67% vs 28%, p = 0.015). The depth of haematological response influenced renal response, obtained in 32 (59%) of evaluable patients, similarly in the subgroups. Indeed, 75% patients with ≥ VGPR (p = 0.049) and none with stable disease (p ≤ 0.001) obtained a renal response. No association between renal response and histotypes (p = 0.9) or type of first‐line therapy (p = 0.3) was found. At a median follow‐up of 54.4 months (IQR 24.8–102.8), median progression‐free survival (PFS) was 100.1 months (95% CI 34.9–NR), and median overall survival not reached (95% CI 129.8–NR). No significant difference emerged between the two groups in terms of survival outcomes. Achieving ≥ VGPR was confirmed as the main independent predictor of prolonged PFS in the general population (HR = 0.29, p = 0.023) and AL amyloidosis group (HR 0.23; p = 0.023). Preserved renal function at diagnosis was predictive of improved PFS in the AL amyloidosis group (eGFR ≥ 60 mL/min: HR = 0.003; p = 0.018; eGFR 30–60 mL/min: HR = 0.04, p = 0.046). Conclusion Further research is warranted to develop standardised response criteria and treatment strategies to improve MGRS management.